Relapse and inadvertent tooth movement post orthodontic treatment in individuals with fixed retainers: A review - Chacón-Moreno, Alicia (2022)
Orthodontists must fully inform patients about the implications of orthodontic treatment and the subsequent need for retention. This review provides an update on relapse, unwanted movements, and different factors that can cause loss of stability following orthodontic treatment. Since it is difficult to predict which patients will present some degree of loss of stability after treatment, it is essential that they be treated as if they have a high potential for relapse. The present review included a bibliographic search in the main sources of scientific review including Medline via PubMed, Scopus, and the Cochrane library. The search strategy was carried out until May 5, 2022. Only 34 studies fulfilled the selection criteria. Our results showed that maintaining teeth in the correct position following orthodontic treatment is a great challenge for orthodontists. The etiology of relapse is complex and not yet clearly established. Its origin is attributed to factors such as the time of gingival and periodontal tissue reorganization and changes produced by growth, compromising the stability of the results achieved with orthodontic treatment. The retention phase is necessary after orthodontic treatment to avoid relapse or loss of the occlusion results obtained. However, fixed retainers may induce unwanted tooth movement that may occur despite these retainers being attached and intact. There is currently no consensus among orthodontists regarding the ideal type of wire for fixed containment. We concluded that post-orthodontic treatment relapse is the result of a regression towards the original malocclusion. However, changes in the position of the teeth can also occur, which are considered as unwanted movements and have a multifactorial origin.